Impact of patient education on plasma concentrations and effectiveness of posaconazole oral suspension under clinical conditions - Geist, Marcus Julian Peter; Egerer, Gerlinde; Mikus, Gerd; Blank, Antje; Hohmann, Nicolas; Carls, Alexandra (Basic & clinical pharmacology & toxicology, 2019)
Posaconazole prophylaxis is recommended for patients with acute myeloid leukaemia during induction chemotherapy. Although a tablet formulation with better oral bioavailability is available, some patients have to rely on the oral suspension in clinical routine. Therefore, effectiveness of posaconazole oral suspension under real-life clinical conditions and impact of patient education about the correct intake on its plasma concentrations were assessed in this study. Altogether 96 patients receiving 160 cycles of induction chemotherapy were retrospectively (40 patients) and prospectively (56 patients) analysed. Patients were assigned into two groups for each chemotherapy cycle according to the application of antifungal prophylaxis (A: posaconazole oral suspension, 200 mg three times a day ≥7 days; B: intake <7 days, fluconazole or no prophylaxis). Antifungal prophylaxis and therapy were analysed for each cycle. Additionally, plasma concentrations were determined from prospectively included subjects of group A who were intensively educated to perform a correct drug intake. Systemic antifungal therapy was statistically started less often in group A (26% vs 53%; P = 0.002). Posaconazole prophylaxis was associated with a lower risk of proven invasive fungal infection (P = 0.003). Median plasma concentration apparently increased between the first and second time of determination effected by an initial intensive on-site patient education. The clinical effectiveness of posaconazole oral suspension was confirmed. A detailed patient education at the beginning of the treatment with posaconazole oral suspensions seems to be of primary importance for efficient plasma concentrations.
First published: 10 July 2018
Gesehen am 05.08.2019